«The Flesh Can Really Partake of Life». (Adv. Haer. V, 3, 3) Clarification of the Use of ζωή in the Writings of Saint Irenaeus - Amo Usanos, Rafael (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
In the present cultural situation, in which everything relating to life is seen to be significant, the theological thought of Irenaeus has come to occupy the position it deserves, as testified by the widespread use of the fortunate expression «the glory of God is a living man». This article seeks to clarify what lies behind the term ζωή in Irenaeus’ thought. The concept of the vital principle is used as a tool to investigate the meanings of ζωή and draw conclusions regarding the application of Irenaeus’ theology to current theological issues. Thus, the article expounds on the meaning of the anthropological terms «soul», «breath» and «spirit» in Irenaeus’ exegeses of the biblical text that the Gnostics read heterodoxically.